Influence of iron doping on the morphological and compositional properties of zirconia foil as photocatalyst / Nor Aimi Abdul Wahab … [et al.] - Abdul Wahab, Nor Aimi; Md Taib, Adhwa Izzati; Shamsol Afandi, Nabilah Yasmin; Isa, Norain; Bashirom, Nurulhuda; Taib, Mustaffa Ali Azhar; Lockman, Zainovia (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Zirconia (ZrO₂) is a promising photocatalyst; however, its performance is often limited by poor charge separation and low visible light absorption. To enhance its photocatalytic potential, this study investigates the effects of iron doping on the morphology and composition of zirconia foil. Iron(II) sulfate heptahydrate (FeSO₄·7H₂O) and iron(III) nitrate nonahydrate (Fe(NO₃)₃·9H₂O) were used at varying concentrations to examine their effects through scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). The findings reveal that higher concentrations of both irons induce notable surface restructuring compounds that cause considerable surface changes and color variations, indicating successful doping among the two precursors, Fe(NO₃)₃·9H₂O exhibits superior doping efficiency at lower concentrations. This study provides qualitative insights into these morphological modifications, contributing to a better understanding of iron-doped zirconia's role in photocatalysis.